Morphology and Molecular Phylogeny of Two New Trachelophyllid Ciliates, Monolamellophrya terricola gen. nov., sp. nov. and Trachelophyllum parapiculatum sp. nov. (Litostomatea, Haptoria), From South Korea - Omar, Atef; Moon, Ji Hye; Jung, Jae-Ho (Frontiers in Microbiology, 2022)
The morphology and molecular phylogeny of two new ciliates, Monolamellophrya terricola gen. nov., sp. nov. and Trachelophyllum parapiculatum sp. nov., discovered from South Korea, were investigated. The two species belong to the suborder Trachelophyllina, which is characterized by the presence of a mucilaginous layer containing lepidosomes covering the cortex. Monolamellophrya terricola gen. nov., sp. nov. is characterized by the presence of a single layer of type II lepidosomes and thus representing a new genus. Trachelophyllum parapiculatum sp. nov. has only type I lepidosomes covering the cortex, a generic character of the genus Trachelophyllum, and is distinguishable from other congeners by a combination of morphological features including the 15–24 μm long rod-shaped extrusomes, the 9–13 ciliary rows, the 7–11 and 17–25 dikinetids in brush rows 1 and 2, respectively, and the bipolar brush row 3. Furthermore, the 18S rRNA gene sequences of the two new species were provided. The phylogenetic analyses show that the sequence of Monolamellophrya terricola gen. nov., sp. nov. clusters with two other trachelophyllid sequences and the sequence of Trachelophyllum parapiculatum sp. nov. is placed at the base of these three sequences with full supports. Also, the four so far available trachelophyllid sequences form a monophyletic clade.